The State of Judicial Scrutiny of Public Contracting in New Zealand and Canada - Mullan, David (Victoria University of Wellington Law Review, 2012)
This article evaluates the varying ways in which the courts of New Zealand and Canada respond to arguments that government procurement exercises are subject to the principles and remedies of public law. While conceding that context is critical and that there are many, often competing considerations that are relevant in the evaluation of such arguments, the author contends that the courts in both countries should at least on occasion be open to the availability of public law remedies for misfired government procurement exercises, and, more importantly, whether by judicial review or civil action, to the deployment of public law principles in the assessment of the procedural and substantive components of government procurement. More generally, the author warns against the movement in both countries in the direction of the assimilation of public procurement within existing principles and remedies of private tendering law.